Existence and Regularity of Solutions for Some Partial Integrodifferential Equations Involving the Nonlocal Conditions. (3rd October 2019) - Ezzinbi, Khalil; Ghnimi, Saifeddine
Abstract: The aim of this work is to prove some results about the existence and regularity of solutions for some partial integrodifferential equations with nonlocal conditions. We suppose that the linear part has a resolvent operator in the sens given by Grimmer. The non linear part is assumed to be continuous and Lipschitzian with respect to the second argument.